RINTISAN PEMBENTUKAN FORUM PEDULI MASYARAKAT DESA “POJOK SAKINAH” DI KELURAHAN TUNJUNGSEKAR KECAMATAN LOWOWARU KOTA MALANG - Sukadi, Imam; Harry, Musleh; Zuhriah, Erfaniah (JRCE (Journal of Research on Community Engagement), 2020)
The implementation of UIN Serving activities in Tunjngsekar Subdistrict, Lowokwaru District of Malang concerning the Establishment of the "Pojok Sakinah" Village Community Care Forum is the first step towards Tunjungsekar Urban District as a legal awareness sub-district. The presence of the "sakinah corner" is expected to be able to educate the community members, provide motivation and as a learning tool, as a place for vent and will eventually lead to people who are obedient and aware of the law. Obstacles in the Establishment of the "Pojok Sakinah" Village Community Care Forum in Tunjungsekar Sub-District, Lowokwaru Sub-District of Malang, among others, the lack of activeness of the Tunjungsekar village government apparatus, lack of coordination with the government officials of Tunjugsekar, Karang Taruna, and the lack of community awareness of the importance of the presence of this Sakinah Corner.